(untitled) (Contemporary Journal of Social Science Review, 2024)
The point of this study was to look into how new green technologies affect the bottom lines of Pakistan’s KMI-30 companies. The study’s main goal is to find out whether green technology innovations have a good or negative effect on firms’ revenue and profits, that is, whether they make firms more or less money. The study uses data from the Karachi Market Index-30 of Pakistan, which is listed on the Pakistan Stock Exchange. The regression method shows that the company’s huge investments in green processes and products caused costs to rise. For that matter, investing in green products and methods might help keep the environment clean and also make money for the business in the long run.